1988
DOI: 10.1016/0014-5793(88)81003-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the vasopressin and oxytocin genes in rats occurs in mutually exclusive sets of hypothalamic neurons

Abstract: The genes for the hypothalamic hormones vasopressin and oxytocin are located in close proximity to each other within the rat genome. They are separated by only approx. 11 kbp of DNA sequence and oriented in such a way that their transcription occurs on opposite DNA strands. Although the two genes are structurally very similar including common potential regulatory elements in their putative promoter regions, they are expressed in discrete populations of magnocellular neurons of the hypothalamus. In rats placed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(50 citation statements)
references
References 22 publications
4
45
0
1
Order By: Relevance
“…The common consensus sequence (CYTTGACC) exhibits the conserved 5 bp motif TGACC, which is known to constitute one half of the estrogen-as well as the thyroid hormone-responsive element (1 9). The human and the rat oxytocin gene promoter contain a sequence with a nearly perfect match to the estrogen-responsive element (15,17). This sequence has been shown to be involved in estrogen-dependent --174, -174 to -167, -159 to -152, -108 to -101, -88 to -81, T A H L~ I .…”
Section: S H Ementioning
confidence: 99%
“…The common consensus sequence (CYTTGACC) exhibits the conserved 5 bp motif TGACC, which is known to constitute one half of the estrogen-as well as the thyroid hormone-responsive element (1 9). The human and the rat oxytocin gene promoter contain a sequence with a nearly perfect match to the estrogen-responsive element (15,17). This sequence has been shown to be involved in estrogen-dependent --174, -174 to -167, -159 to -152, -108 to -101, -88 to -81, T A H L~ I .…”
Section: S H Ementioning
confidence: 99%
“…There are a number of variations on this method, but most procedures employ radiolabelled complementary DNA or R N A probes which can only be visualized by autoradiography. Autoradiographic procedures used on their own are not well suited t o studies of the possible co-existence or co-expression of two mRNAs in one cell and in order to d o this either a combination of radiolabelled and non-radiolabelled complementary probes (2), o r a combination of two non-radiolabelled probes which can be detected by different coloured reporter molecules has to be used (3). In an initial study using two non-radioactive in situ probes ( 3 ) we found that the majority (> 95%) of magnocellular neurosecretory cells in osmotically-stressed rats contained only one transcript (either oxytocin or vasopressin).…”
mentioning
confidence: 99%
“…Based on biochemical, morphological and physiological criteria, the HNS neuronal population has been historically divided into two distinct phenotypes, the OT and VP neurons [53, 54]. The two neuronal phenotypes in rats have also been discriminated by their distinct electrical properties [44, 45, 46, 47].…”
Section: Ot and Vp Gene Expression In The Hypothalamusmentioning
confidence: 99%